Three men and two villages: the influence of footballers from rural South Yorkshire on the early development of the game in Sheffield. (2nd January 2018) - Neill, Kevin; Curry, Graham; Dunning, Eric
Abstract : This article adds to the narrative of the early Sheffield football subculture. It suggests that there were three main strands of diffusion through which the game developed in and around the city – the ideas of the former pupils of Sheffield Collegiate School, one of which, Nathaniel Creswick, became a co-founder of Sheffield FC, the first club side; the minimal influence from the major public schools, with whom members of Sheffield FC communicated; individuals involved in local forms of the game in the Penistone/Thurlstone area to the north of the city. The authors highlight the part played by several individuals, specifically John Dransfield, in this process.